Effectiveness of EDP-STEM to Empower Higher Order Thinking Skills in Physics Learning : A Meta-analysis - Nurmasyitah; Erlangga, Sony Yunior; Fitriyah, Isnanik Juni (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
Higher Order Thinking Skills (HOTS) are essential competencies in the 21st century. Although many studies have examined Engineering Design Process-STEM (EDP-STEM), there is still limited synthesis of its effectiveness in physics learning. This study applied a systematic review using the PRISMA protocol and synthesized nine empirical studies published between 2019 and 2024. Data were analyzed with a random-effects model. The overall effect size was 0.64 (95% CI [0.17–1.11], I² = 86%), indicating a moderate positive impact of EDP-STEM on students’ HOTS. Moderator analysis revealed that learning media (prototyping), education level (high school), and performance-based assessments produced the most significant effects. EDP-STEM effectively enhances HOTS in physics learning, particularly problem-solving skills. Teachers are encouraged to integrate prototyping and authentic assessment strategies. Future research should expand the number of studies and contexts to strengthen the evidence base.